The benefit of urban green area in Kota Kinabalu, Sabah - Andy Russel Mojiol; W S Lim; K C L Chung; J L Dani (IOP Publishing, 2021)
The city of Kota Kinabalu features several urban green areas, which become the focal points for the urban inhabitants. This study was conducted to determine the benefits and public perceptions that encourage them to visit the local urban green area. The convenience sampling method was used, in which questionnaires were distributed to 101 respondents of the local park visitors. The present finding revealed that most of the respondents strongly agreed that the urban greens help to improve the physical well-being of the urban dwellers (Mean score, µ=4.27), regulate the urban temperature during sunny days (µ=4.20), encourage people to spend more time on outdoor activities in nature (µ=4.14), help to remove air pollutants (µ=4.09), control the amount of water on the ground surface during the rainy season (µ=4.06), reduce stress, anxiety, and depression (µ=4.04), prevent the occurrence of a flash flood (µ=3.98), and promote social interactions among people (µ=3.81). The correlation between the respondents’ education and the mean benefits of urban green areas in Kota Kinabalu was significant (p<0.05). In conclusion, the public perception of the benefits of urban green areas is generally positive, and they also exhibit a high understanding of its importance towards urban dwellers.